Genetic Structure of the Endangered Coral Cladocora caespitosa Matches the Main Bioregions of the Mediterranean Sea - Repullés, Mar; López-Márquez, Violeta; Templado, José; Taviani, Marco; Machordom, Annie (Frontiers in Genetics, 2022)
Population connectivity studies are a useful tool for species management and conservation planning, particular of highly threatened or endangered species. Here, we evaluated the genetic structure and connectivity pattern of the endangered coral Cladocora caespitosa across its entire distribution range in the Mediterranean Sea. Additionally, we examined the relative importance of sexual and asexual reproduction in the studied populations and their genetic diversity. A total of 541 individuals from 20 localities were sampled and analysed with 19 polymorphic microsatellite markers. Of the genotyped individuals, 482 (89%) had unique multilocus genotypes. Clonality percentages of the populations varied from 0% (in eight populations) to nearly 69% (in one from Crete). A heterozygosity deficit and a high degree of inbreeding was the general trend in our data set. Population differentiation in C. caespitosa was characterised by significant pairwise FST values with lower ones observed at an intraregional scale and higher ones, between populations from different biogeographic regions. Genetic structure analyses showed that the populations are divided according to the three main sub-basins of the Mediterranean Sea: the Western (Balearic, Ligurian and Tyrrhenian seas), the Central (Adriatic and Ionian seas) and the Eastern (Levantine and Aegean seas), coinciding with previously described gene flow barriers. However, the three easternmost populations were also clearly separated from one another, and a substructure was observed for the other studied areas. An isolation-by-distance pattern was found among, but not within, the three main population groups. This substructure is mediated mainly by dispersal along the coastline and some resistance to larval movement through the open sea. Despite the low dispersal ability and high self-recruitment rate of C. caespitosa, casual dispersive events between regions seem to be enough to maintain the species’ considerable genetic diversity. Understanding the population connectivity and structure of this endangered scleractinian coral allows for more informed conservation decision making.